2016
DOI: 10.1007/s13277-016-4850-3
|View full text |Cite
|
Sign up to set email alerts
|

Roles of CDKN1A gene polymorphisms (rs1801270 and rs1059234) in the development of cervical neoplasia

Abstract: The CDKN1A gene product is a p53 downstream effector, which participates in cell differentiation, development process, repair, apoptosis, senescence, migration, and tumorigenesis. The objective of our study was investigated the importance of two polymorphisms in the CDKN1A gene, rs1801270 (31C>A) and rs1059234 (70C>T), for the development of cervical lesions in a Southeastern Brazilian population (283 cases, stratified by lesion severity, and 189 controls). CDKN1A genotyping was performed by polymerase chain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 42 publications
0
14
1
Order By: Relevance
“…In Chinese and in non-Asian women, the missense variant c.93C > A located in codon 31 was associated with protective effects against cervical cancer [83,84]. In the Brazilian population, c.93C > A and c.*20C > T (located in 3 0 UTR) variants of CDKN1A were also associated with protection against cervical cancer [85]. CDKN1A was found to be hypermethylated in less than 10% of cervical cancer samples [31].…”
Section: Cell Cycle Regulation and Dna Repairmentioning
confidence: 94%
“…In Chinese and in non-Asian women, the missense variant c.93C > A located in codon 31 was associated with protective effects against cervical cancer [83,84]. In the Brazilian population, c.93C > A and c.*20C > T (located in 3 0 UTR) variants of CDKN1A were also associated with protection against cervical cancer [85]. CDKN1A was found to be hypermethylated in less than 10% of cervical cancer samples [31].…”
Section: Cell Cycle Regulation and Dna Repairmentioning
confidence: 94%
“…p21 is the major downstream effector of p53, which can act as a mediator between p53, DNA damage and repair and cell-cycle inhibition. 33 Due to the complex function of p21, p21 exhibits both tumor suppressor and oncogenic attributes. 34 Several studies have been reported the effects of P21 polymorphisms on the function of its protein and may contribute to cancer susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…p21 is the major downstream effector of p53, which can act as a mediator between p53, DNA damage and repair and cell‐cycle inhibition . Due to the complex function of p21, p21 exhibits both tumor suppressor and oncogenic attributes .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies show an association between CDKN1A -SNPs and cancer and patient survival prognostics (e.g. Cazier et al 2014 ; Kang et al 2015 ; Vargas-Torres et al 2016 ). A recent study of Price et al ( 2015 ) suggests that CDKN1A regulates Langerhans cell and could influence the response of cutaneous tumours to radiotherapy.…”
Section: Introductionmentioning
confidence: 99%